CONTENT ANALYSIS OF INSTAGRAM SOCIAL MEDIA ACCOUNTS @3SECOND LOCAL BRAND FASHION PRODUCTS - Aditya Rizka Ramadhanta; Nur Maghfirah Aesthetika (International Journal of Economic Integration and Regional Competitiveness, 2024)
General Background: The rise of social media has fundamentally transformed consumer behavior, particularly in the fashion industry, where brands leverage platforms like Instagram to engage with consumers. Specific Background: Established in Indonesia in 2012, 3second has positioned itself as a prominent local brand within the casual wear segment, gaining traction through trendy designs and affordability. Knowledge Gap: Despite its growth, there is limited research analyzing the specific impact of 3second’s social media strategy on consumer perceptions and engagement within the local market. Aims: This study aims to conduct a content analysis of the Instagram account @3second to explore the nature of consumer interactions and the brand's influence on consumer attitudes toward local fashion products. Results: The analysis reveals that content shared on the @3second Instagram account is generally well-received, generating positive feedback from consumers. Key factors contributing to this positive reception include trendy designs, perceived quality, and affordability. Novelty: This study contributes to the literature by providing empirical insights into how local fashion brands in Indonesia utilize social media to cultivate consumer loyalty and brand recognition. Implications: The findings underscore the importance of engaging with consumers through interactive content and prompt responses, suggesting that local brands can enhance their market presence by effectively leveraging social media platforms to align with consumer preferences and trends.